It's Raining Right Now: God's Love as Pouring Out in the Christian Contemplative Tradition - Thralls, Chad (Studies in spirituality, 2025)
In this piece, I explore some key moments in the development of a particular mystical theme: God’s love as pouring out, especially the pouring out of a liquid. This image addresses the relationship between the gift of divine presence and the human effort necessary to become aware or conscious of this gift. My intention here is not to provide a comprehensive introduction, but to highlight a few notable examples of the use of this theme that underscore its power to evoke intimacy with the divine. After treating the thoughts of Teresa of Avila, Meister Eckhart, Thomas Merton and Mechtild of Magdeburg on this theme, I conclude the paper by highlighting a mental habit that occasionally prevents me from experiencing the continual outpouring of the love of God, using a recent Academy Award winning short film and my own experience as examples.